Peningkatan kemampuan menganalisis unsur intrinsik naskah drama menggunakan model kooperatif - Br Bangun, Egitamersa Yolanda; Saragih, Erikson (citeus, 2020)
The purpose of this research to improve the ability to analyze the intrinsic elements of the drama in students of class VIII-2 Private Junior High School Nurcahaya Medan using a jigsaw type cooperative learning model. The drama script is an essay containing stories or plays. The drama script is inseparable from the intrinsic element of the drama script. Jigsaw type cooperative learning model is a cooperative learning model where students work collaboratively in small groups consisting of four to six people heterogeneously. This research is a classroom action research, conducted at Private Junior High School Nurcahaya Medan. The stages of the study were divided into two cycles, each of which was implemented within the time allocation of 3x40 minutes. Subjects in this study were 33 students of class VIII-2. The data analysis technique was conducted by a qualitative descriptive analysis technique. The results of the study show an increase, i.e., in the assessment of the first cycle of 60,76 to 76,82 in the second cycle. Students who completed the first cycle were 11 students and increased to 26 students on the second cycle.